ANALISIS STATIK KEKUATAN STRUKTUR FITTING PADA LANDING GEAR PADA PESAWAT N-219 - Muhamad Jalu Purnomo (Institut Teknologi Dirgantara Adisutjipto, 2017)
Aircraft structures to be made stronger in order to be able to withstand the force received. The forces acting on the structure can cause deformation and result in structural failure. All components o f the structure o f the aircraft is an important part and it requires a good working resilience to maintain the security (safety). One important component of the aircraft that must be considered is the structure of the landing gear fittings. Fitting is contained in the structure that functions held their landing gear load received all the landing gear and as an intermediary for the landing gear and airframe structure of the aircraft. Because Landing Gear is one important component in the structure of the aircraft. Strength landing gear fittings will be calculated at the time of landing, the burden derived from the speed of the aircraft landing and aircraft load.